2011
DOI: 10.1105/tpc.110.080804
|View full text |Cite
|
Sign up to set email alerts
|

MATE2 Mediates Vacuolar Sequestration of Flavonoid Glycosides and Glycoside Malonates inMedicago truncatula     

Abstract: The majority of flavonoids, such as anthocyanins, proanthocyanidins, and isoflavones, are stored in the central vacuole, but the molecular basis of flavonoid transport is still poorly understood. Here, we report the functional characterization of a multidrug and toxin extrusion transporter (MATE2), from Medicago truncatula. MATE 2 is expressed primarily in leaves and flowers. Despite its high similarity to the epicatechin 39-O-glucoside transporter MATE1, MATE2 cannot efficiently transport proanthocyanidin pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
278
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(291 citation statements)
references
References 81 publications
(148 reference statements)
8
278
0
Order By: Relevance
“…The anthocyanin malvidin-3-O-glucoside is transported into vacuoles of grape (Vitis vinifera) berries by the ABCC transporter ABCC1 from grape (Francisco et al, 2013). Proton gradient-dependent vacuolar transport mechanisms were reported for diverse flavonoid glucosides (Klein et al, 1996;Frangne et al, 2002;Zhao and Dixon, 2009;Zhao et al, 2011). Moreover, the vacuolar import mechanism of particular Glc conjugates was found to be species or tissue specific.…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…The anthocyanin malvidin-3-O-glucoside is transported into vacuoles of grape (Vitis vinifera) berries by the ABCC transporter ABCC1 from grape (Francisco et al, 2013). Proton gradient-dependent vacuolar transport mechanisms were reported for diverse flavonoid glucosides (Klein et al, 1996;Frangne et al, 2002;Zhao and Dixon, 2009;Zhao et al, 2011). Moreover, the vacuolar import mechanism of particular Glc conjugates was found to be species or tissue specific.…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 99%
“…Members of the MATE transporter superfamily have been shown to mediate the proton-dependent vacuolar sequestration of flavonoid glucosides (Marinova et al, 2007;Zhao and Dixon, 2009;Zhao et al, 2011). In Arabidopsis, the MATE superfamily consists of 56 members (The Arabidopsis Genome Initiative, 2000).…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 99%
“…These metabolites may otherwise display adverse activities for the producing plant cell. Intracellular storage of such biologically active metabolites in the vacuole is well established for water-soluble compounds and for compounds that become water soluble through conjugation (Marinova et al, 2007;Ferreres et al, 2011;Zhao et al, 2011;Li et al, 2012b). Similarly, for the large class of often-lipophilic terpenoids, it has been suggested that their intracellular accumulation may be limited by nonspecific interference with cellular Figure 6.…”
Section: In Planta Heterologous Expression and Functional Characterizmentioning
confidence: 99%
“…When expressed in barrel medic (Medicago truncatula) hairy roots (HRs), Arabidopsis TT12 as well as a MATE transporter of barrel medic, MATE1, transport the proanthocyanidin (PA) precursor epichatechin 3-Oglucoside (Zhao and Dixon, 2009). A second barrel medic MATE transporter, MATE2, was shown to have consistently different substrate specificity despite its high similarity to MATE1; it efficiently catalyzes the vacuolar uptake of malonylated anthocyanins, while transporting glycosylated anthocyanidins at a lower rate (Zhao et al, 2011). More recently, two grapevine (Vitis vinifera) MATEs, AM1 and AM3, have been described to specifically transport acylated anthocyanins, but not glucosylated ones, which are the predominant forms that accumulate in berries of most red grapevine cultivars .…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the transporter-mediated model, biochemical, molecular, and genetic evidence support the involvement of both multidrug and toxic extrusion (MATE) and the ATP binding cassette (ABC) proteins in the transport of anthocyanins (Goodman et al, 2004;Marinova et al, 2007b;Gomez et al, 2009;Zhao and Dixon, 2009;Zhao et al, 2011). MATE transporters comprise a large family of transporters, widely distributed in all living organisms.…”
Section: Introductionmentioning
confidence: 99%